Proceedings on the review and early results workshop: Centre on integrated rural development for Asia and the Pacific (CIRDAP) - Chowdhury, Sulin (International Food Policy Research Institute, 2017)
Holding a review and early results workshop event was proposed by the project office during a meeting in late February of 2017. The two primary objectives of the workshop event were to (a) disseminate information about the progress of IFPRP’s activities and (b) receive feedback and inquiries regarding said activities. Another objective of the workshop was to give a space for members of every attending institution (both government and private) to communicate and share information with one another. The Center for Integrated Rural Development for the Asia and Pacific (CIRDAP) was identified as an ideal venue for the event.